Understanding COVID‐19 misinformation and vaccine hesitancy in context: Findings from a qualitative study involving citizens in Bradford, UK. (4th May 2021) - Lockyer, Bridget; Islam, Shahid; Rahman, Aamnah; Dickerson, Josie; Pickett, Kate; Sheldon, Trevor; Wright, John; McEachan, Rosemary; Sheard, Laura; ,
Abstract: Background: COVID‐19 vaccines can offer a route out of the pandemic, yet initial research suggests that many are unwilling to be vaccinated. A rise in the spread of misinformation is thought to have played a significant role in vaccine hesitancy. To maximize uptake, it is important to understand why misinformation has been able to take hold at this time and why it may pose a more significant problem within certain contexts. Objective: To understand people's COVID‐19 beliefs, their interactions with (mis)information during COVID‐19 and attitudes towards a COVID‐19 vaccine. Design and Participants: Bradford, UK, was chosen as the study site to provide evidence to local decision makers. In‐depth phone interviews were carried out with 20 people from different ethnic groups and areas of Bradford during Autumn 2020. Reflexive thematic analysis was conducted. Results: Participants discussed a wide range of COVID‐19 misinformation they had encountered, resulting in confusion, distress and mistrust. Vaccine hesitancy could be attributed to three prominent factors: safety concerns, negative stories and personal knowledge. The more confused, distressed and mistrusting participants felt about their social worlds during the pandemic, the less positive they were about a vaccine. Conclusions: COVID‐19 vaccine hesitancy needs to be understood in the context of the relationship between the spread of misinformation and associated emotional reactions. Vaccine programmes should provide a focused, localized and empathetic response to counter misinformation. Patient or Public Contribution: A rapid community and stakeholder engagement process was undertaken to identify COVID‐19 priority topics important to Bradford citizens and decision makers.